A systematic review on methods of optimizing riser and gating system based on energy Nexus approach - Jalaj Bhatt (Elsevier, 2021)
Casting industries play a crucial role in various industrial sectors like Defence, Automotive sectors, Construction, Agriculture, Aerospace, Oil & Gas (energy sector), Mining, Railroad, Water infrastructure, Transportation, and Health & Medical care. The review article integrates various algorithms, methods, and processes to design an industrially accepted, scientifically sound, reliable feeding system. This systematic review brings out the use of different software used in industry to create and analyze the overall casting process like PRO-cast, MAGMASOFT, ANSYS, CAD software, etc. It also highlights various gating systems for many vital metals and alloys like AZ91, Al-12Si, steel, etc. Moreover, it gives an insight into the casting technology for manufacturing profound components of industrial locomotives and machines like turbine housing, large full-spade carrier housing with axisymmetric large offshore structures with the optimization of the gating system. It concludes that designing a sound feeding system is possible by adequate mathematical tools and numerical simulations.